Method of optimization for elastic damping suspensions - Павлюченко, Виталий Александрович; Стрельникова, Елена Александровна; Филипковский, Сергей Владимирович (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
The design of equipment at overloads in aircrafts requires effective methods for analyzing the vibration characteristics of suspensions, as well as the developing the synthesis methods to solve the topical problems. For these purposes the adaptive hybrid optimization method is developed. The objects of optimization are different suspensions of space-crafts and aircrafts units with asymmetrical distribution of masses and different arrangement of joints. Joints are the attachment points in the form of shock absorbers and bellows for joining with pipes. Blocks are considered as solid bodies. The links are highlighted as optimized elements. The main objective of the research is to improve the method of optimizing the parameters of shock absorbers that have to provide protection from vibrations and operating shock loads. The proposed optimization method uses a number of different methods that are operated together. Different criteria and their combination are chosen. These criterions include and overwork information that characterizes the changing situations; namely, mechanical and geometric information about structures, metric parameters of the space where the search is carried out, the prehistory of the computational process by which the possible continuation is established, and nature of the functions system that determine the problem under consideration. Adaptive control is introduced, and it obtains decision vectors, search directions and search steps, respectively to the changing situations. It is possible to effectively minimize the mass of system only with minimization of overload which is the variable parameter. Its boundary determines the domain where the search process of solution is accomplished. So, it is natural to use multi-criteria optimization. In this case, at the same time the optimization of masses and overloads is in progress. Restrictions are imposed on the structural dimensions and strength characteristics of the shock absorbers. As a result of the optimization, the weight of the suspension elements and the overload acting on the suspended block are reduced. The limits are determined of mass and overload diminishing.